Analisis Kestabilan Model Host-Vector Transmisi HIV/AIDS Pada Pengguna Jarum Suntik - (Alm), Jafaruddin; Pangaribuan, Rapmaida M.; Aryanto, ,; Henukh, Irena A. (Jurnal Matematika, 2022)
HIV/AIDS is a very dangerous disease. The transmission of  HIV/AIDS can be in three ways  and one of them through a syringe. In this paper we describe SIR and SEIR Host-Vector  model transmission of HIV/AIDS amongst populations of  injecting drug users. From the existing model we obtained disease-free equilibrium  point and endemic equilibrium point. Then we study the stability conditions and sensitivity analysis of the  . The analysis shows if   then the disease-free equilibrium  point is stable and if    then the endemic equilibrium point will be stable. We also obtained that parameter of probality host-vector infected with HIV/AIDS affects the increase of  number  infected HIV/AIDS. Keywords : HIV/AIDS, Host-Vector Transmission, The Stability of Equilibrium Point.